Penyediaan Fasilitas Ramah Tamah Penyandang Disabilitas sebagai Wujud Kepedulian Pemerintah : (Studi Kasus: ditinjau dari Badan Pertanahan Nasional (BPN)) - Bella Ayu Anzalia; Martua Felix Jonatan Simanullang; Nike Margaretha BR Sembiring; Sarah Lestari Tampubolon; Pingky Monica Hasugian; Halimah Halimah; Friska Lorentina Purba; Taufiq Ramadhan (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
The provision of friendly facilities for people with disabilities is one form of government concern in creating social inclusion and equal access for all levels of society. In this context, the National Land Agency (BPN) plays an important role in ensuring that public facilities provided can be accessed by all individuals, including people with disabilities. This study aims to analyze how BPN provides disability-friendly facilities at the regional office located on Jalan STM, Sitirejo, Medan Amplas District, Medan City, North Sumatra. This study uses a qualitative approach with an in-depth case study method, where data is obtained through interviews, direct observation, and documentation studies related to the provision of facilities for people with disabilities at the BPN. The results of the study indicate that despite efforts by the BPN to provide facilities that are friendly to people with disabilities, there are still a number of obstacles that need to be fixed, such as the lack of supporting facilities such as disabled lanes, and information on service procedures that are not fully disability-friendly. From this study, it is recommended that the BPN can improve infrastructure and services for people with disabilities by paying attention to applicable standards, and conduct wider socialization related to accessibility rights for people with disabilities, in order to realize more inclusive public services.